„Barwy Białe” w drodze na pomoc walczącej Warszawie. Zbrodnie AK na Żydach - Skibińska, Alina; Mazurek, Jerzy (Zagłada Żydów. Studia i Materiały, 2011)
The soldiers of “Barwy Białe” Home Army partisan detachment created at the end of 1943 in the Opatów district participated in at least a few murders of Jews – the murders in Goździelin, Lisów and Siekierzyn forests are documented. The last crime, committed on 16 or 17 August 1944 when the detachment (at that time a part of the 2nd Infantry Division) was marching to aid warring Warsaw (as part of Operation Tempest). While quartered in Siekierno, the detachment’s commanding officer Kazimierz Olchowik “Zawisza” issued an order to execute a big group of Jews (30–58 people) living in the nearby forests after their escape from the labor camp in Skarżysko-Kamienna. After World War II most participants of the murders were tried and punished. No punishment, however, was administered to the detachment’s commanding officer Kazimierz Olchowik and to the sergeant by the pseudonym “Bolrok” – the two chiefly responsible for the murder in the Siekierzyn forests.